Curriculum Management System in Religious Education: Insights from Diniyah Takmiliyah Al-Wahdah, Bandung City - Taufik Maulana; Andriyani Andriyani; Masyitoh Chusnan; Armai Arief; Muhammad Husni Abdulah Pakarti (International Journal of Nusantara Islam, 2023)
Within the realm of religious education and the national educational framework, Diniyah Takmiliyah (DT) stands as a pivotal cornerstone in the nation’s development, preparing future generations with a robust grounding in religious knowledge, profound insight, life skills, and virtuous character, all rooted in a deep understanding of Islamic teachings. Diniyah Takmiliyah Al-Wahdah in Bandung city is not only a prominent exemplar within the city but also within the wider context of West Java and Indonesia. This research endeavors to delve into the Implementation of the Curriculum Management System within the Diniyah Takmiliyah Education at Al-Wahdah Bandung city. Employing a qualitative research approach, this study aims to shed light on the practical application of the curriculum management system in Diniyah Takmiliyah Al-Wahdah Bandung city. Qualitative research, characterized by its inductive nature, primarily seeks to depict and explore. The research methodology entails field research, involving direct data collection in the field. The research subjects, serving as primary data sources, encompass all individuals contributing information necessary for comprehensive data collection. These individuals consist of the Diniyah Head, Teachers, and students, selected through purposive sampling, with the sampling technique employing a snowball sample. The research findings reveal that Diniyah Takmiliyah Al-Wahdah Bandung city stands as a distinguished and paradigmatic institution within Bandung city. In its practical implementation, the institution amalgamates the Diniyah Takmiliyah curriculum with the Islamic Religious Education curriculum of Elementary Schools or Madrasah Ibtidaiyah, seamlessly integrating them within the framework of the curriculum at Diniyah Takmiliyah Al-Wahdah Bandung city